Полужесткокрылые рода Aradus группы betulae (Heteroptera, Aradidae) фауны СССР - Канюкова, Е.В. (Вестник зоологии, 1984)
10 species of the Aradus betulae group are considered. Key to species, male genitalia described and figured, data on distribution and range. A. hercu- leanus is established to be a distinct species. A. ribauti and A. krueperi for the first time are shown for the USSR territory. A. persicus, A. marginatus and A. turkestanicus are considered as subspecies of A. caucasicus.